Sostenibilidad corporativa y rendimiento para los accionistas: un estudio comparativo sobre el rendimiento de las acciones que componen el índice B3 de sostenibilidad corporativa - Godinho Serra, Alessandra (2023)
This article aims to answer the following question: Do companies with sustainable initiatives bring a greater return to shareholders? The authors have built a hypothetical portfolio based on the B3 Corporate Sustainability Index (ISE) methodology through an ex-post facto descriptive research. The authors have also calculated the beta and weighted returns considering each share weight and the proportional impact on the portfolio. The alpha calculation and the association with the Student 's t-test allowed investigation on the possibility of an incremental return concerning the adopted reference. We have concluded that the responsible investment strategy in companies considered sustainable, through the hypothetical portfolio, does not bring the possibility of an incremental return to the shareholder when compared to the market portfolio. On the other hand, the hypothetical portfolio does not bring a return lower than the market portfolio. That is, its performance does not fall short.